Natural mega disturbances drive spatial and temporal changes in diversity and genetic structure on the toadfish Aphos porosus - Cynthia Vásquez; Iván Vera-Escalona; Antonio Brante; Francisco Silva; Eduardo Hernández-Miranda (Scientific Reports, 2023)
Abstract Natural disturbances can modify extinction-colonization dynamics, driving changes in the genetic diversity and structure of marine populations. Along Chilean coast (36°S, 73°W), a strong hypoxic-upwelling event in 2008, and a mega earthquake-tsunami in 2010 caused mass mortality within the Aphos porosus population, which is a vulnerable species with low dispersal potential. We evaluated the effects of these two major disturbances on the diversity and spatial-temporal genetic structure of Aphos porosus in two neighboring areas that were impacted on different levels (High level: Coliumo Bay; Low level: Itata Shelf). Thirteen microsatellites (from 2008 to 2015) amplified in individuals collected from both locations were used to evaluate the effects of the two disturbances. Results showed that after the strong hypoxic-upwelling event and the mega earthquake-tsunami, Aphos porosus populations exhibited lower genetic diversity and less effective population sizes (Ne < 20), as well as asymmetries in migration and spatial-temporal genetic structure. These findings suggest a rise in extinction-recolonization dynamics in local Aphos porosus populations after the disturbances, which led to a loss of local genetic diversity (mainly in Coliumo Bay area impacted the most), and to greater spatial-temporal genetic structure caused by drift and gene flow. Our results suggest that continuous genetic monitoring is needed in order to assess potential risks for Aphos porosus in light of new natural and anthropogenic disturbances.